SIMULATION OF CRYOGENIC DISTILLATION OF ATMOSPHERIC AIR USING ASPEN HYSYS. Issue 1 (2022) - Yerolla, Raju; Muhammed, Ramzal C A; Naseef, Y; Besta, Chandra Shekar
Abstract: Nitrogen has significant commercial and scientific importance in both its gaseous and liquid states. The atmosphere is a rich source of the same, and it can be used as a raw material to obtain it. However, the technology and the possibility of implementing specific procedures and machinery appear to be difficult. In this scenario, cryogenic distillation is used to separate nitrogen from atmospheric air in its purest form. Aspen HYSYS is used for steady-state and dynamic simulation of the process. The goal of the simulation is to find the best process parameters and thus the purest form of nitrogen. Simulation studies of steady and dynamic states are carried out. Product purity, molar flowrate, product recovery, specific power, and various behaviors depending on control setup will be researched.